Ta có:
\(a^2+b^2\ge2ab\)
\(b^2+1\ge2ab\)
\(\Rightarrow a^2+2ab^2+3\ge2\left(ab+b+1\right)\)
\(\Rightarrow\dfrac{1}{a^2+2b^2+3}< \dfrac{1}{2.\left(ab+b+1\right)}\)
Tương tự:
\(\dfrac{1}{a^2+2b^2+3}+\dfrac{1}{b^2+2c^2+3}+\dfrac{1}{c^2+2a^2+3}\le\dfrac{1}{2}.\left(\dfrac{1}{ab+b+1}+\dfrac{1}{bc+c+1}+\dfrac{1}{ca+a+1}\right)\)
Mặt khác:
\(\dfrac{1}{ab+b+1}+\dfrac{1}{bc+c+1}+\dfrac{1}{ca+a+1}=\dfrac{1}{ab+b+1}+\dfrac{ab}{ab^2c+abc+ab}+\dfrac{b}{bca+ab+b}=1\)
\(\Rightarrow\dfrac{1}{a^2+2b^2+3}+\dfrac{1}{b^2+2c^2+3}+\dfrac{1}{c^2+2a^2+3}\le\dfrac{1}{2}\)
\(\Leftrightarrow a=b=c=1\)
\(\Rightarrow\) Đpcm.
Áp dụng BĐT AM - GM, ta có:
\(a^2+2b^2+3\)
\(=\left(a^2+b^2\right)+\left(b^2+1\right)+2\)
\(\ge2ab+2b+2\)
Tương tự, ta có: \(b^2+2c^2+3\ge2bc+2c+2\) và \(c^2+2a^2+3\ge2ac+2a+2\)
\(VT=\dfrac{1}{a^2+2b^2+3}+\dfrac{1}{b^2+2c^2+3}+\dfrac{1}{c^2+2a^2+3}\)
\(\le\dfrac{1}{2ab+2b+2}+\dfrac{1}{2bc+2c+2}+\dfrac{1}{2ac+2a+2}\)
\(=\dfrac{1}{2}\left(\dfrac{1}{ab+b+1}+\dfrac{1}{bc+c+1}+\dfrac{1}{ac+a+1}\right)\)
\(=\dfrac{1}{2}\left(\dfrac{1}{ab+b+1}+\dfrac{abc}{bc+c+abc}+\dfrac{abc}{ac+a^2bc+abc}\right)\) (Thay abc = 1)
\(=\dfrac{1}{2}\left(\dfrac{1}{ab+b+1}+\dfrac{ab}{b+1+ab}+\dfrac{b}{1+ab+b}\right)\)
\(=\dfrac{1}{2}\times\dfrac{1+ab+b}{ab+b+1}\)
\(=\dfrac{1}{2}=VP\left(\text{đ}pcm\right)\)
Dấu "=" xảy ra khi a = b = c = 1